Nursing asistence to the bearer of alterations in the cutaneous integrity: a learning education experience account - Marin, Maria José Sanches; Vilela, Elaine Morelato; Takeda, Elisabete; Santos, Ione Ferreira (Revista da Escola de Enfermagem da USP, 2002)
The Nursing Course at the Medicine College in Marília, has been making every efforts to create the Integrate Curiculum, making use of the questionable methodology. In this study, the authors present the student' expected performances and the sequency of activities creat to teach the precautions of Nursing for the adult and elder people taking away some changes na the cutaneous integrity, that makes the student implement the konowlege. During the activities it was proved that this kind of challenge has showed a progress in the teachin and learning process, but there are some difficulties to be conquered.